Kebijakan Kepala Sekolah dalam Meningkatkan Kualitas Belajar Peserta Didik di Madrasah Ibtidaiyah Swasta Nurus Salam - Muhammad Iqbal; Dika Triatmaja; Bening Luhur Junani; Dinda Syafira; Vivin Fitriani (Journal on Education, 2023)
Education is an important thing in determining individual self-development, and for the life of a nation, the important role of education is one of the drivers of the progress of a nation. The educational policy at the Nurus Salam Private Madrasah Ibtidaiyah also requires school members to comply with regulations. The research method that we use is descriptive qualitative research. Namely research that uses a qualitative approach in collecting data. Which is then used in the form of a description. This study seeks to describe the policies in improving the learning quality of students at the Nurus Salam Private Madrasah Ibtidaiyah. Research informants included Madrasah Principals and Private Madrasah Ibtidaiyah Teachers. The techniques we use to collect the data are observation, interviews and document analysis.